2015
DOI: 10.1111/ejss.12314
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria as transporters of phosphorus through soil

Abstract: Summary The transport of phosphorus (P) from agricultural land has led to the eutrophication of surface waters worldwide, especially in areas with intensive animal production. In this research, we investigated the role of bacteria in the leaching of P through three agricultural soils with different textures, before and after the surface application of dairy slurry manure (Bos taurus L.). Leachates of intact soil columns (diameter 20 cm, height 20 cm) of loamy sand, sandy loam and loam were analysed for total b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…It is also suggested that in the absence of microbial participation, most stress environments are not conducive to phosphorus uptake and transport. Most stressful environments that promote phosphorus uptake and transport in plant roots may be directly related to rhizosphere microorganisms (Glaesner et al, 2016).…”
Section: Root Secretion and Soil Phosphorus Utilizationmentioning
confidence: 99%
“…It is also suggested that in the absence of microbial participation, most stress environments are not conducive to phosphorus uptake and transport. Most stressful environments that promote phosphorus uptake and transport in plant roots may be directly related to rhizosphere microorganisms (Glaesner et al, 2016).…”
Section: Root Secretion and Soil Phosphorus Utilizationmentioning
confidence: 99%
“…Notwithstanding, the standard and most common management practice for manures, whether raw or dried, is land application without any necessary pathogen treatment in contrast to sewage sludge application (i.e., so-called "biosolids"), which typically require pretreatment (Loyon et al, 2016;Loyon, 2018). This, however, provides routes by which pathogens can contaminate natural environments, food crops, animals, and humans (Bradford et al, 2006;Glaesner et al, 2015;Muirhead et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is also a component of RNA, the compound that reads the DNA genetic code to build proteins and other compounds essential for plant structure and seed yield. (Johnston, 2001;Brady, 1990;Goldstein et al, 1998;El-Ghamry et al, 2009 andGlaesner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%